Ascorbic acid improves parthenogenetic embryo development through TET proteins in mice. Issue 1 (11th January 2019) - Gao, Wei; Yu, Xianfeng; Hao, Jindong; Wang, Ling; Qi, Minghui; Han, Liang; Lin, Chao; Wang, Dongxu
Abstract : The TET (Ten-Eleven Translocation) proteins catalyze the oxidation of 5mC (5-methylcytosine) to 5hmC (5-hydroxymethylcytosine) and play crucial roles in embryonic development. Ascorbic acid (Vc, Vitamin C) stimulates the expression of TET proteins, whereas DMOG (dimethyloxallyl glycine) inhibits TET expression. To investigate the role of TET1, TET2, and TET3 in PA (parthenogenetic) embryonic development, Vc and DMOG treatments were administered during early embryonic development. The results showed that Vc treatment increased the blastocyst rate (20.73 ± 0.46 compared with 26.57 ± 0.53%). By contrast, DMOG reduced the blastocyst rate (20.73 ± 0.46 compared with 11.18 ± 0.13%) in PA embryos. qRT-PCR (quantitative real-time PCR) and IF (immunofluorescence) staining results revealed that TET1, TET2, and TET3 expressions were significantly lower in PA embryos compared with normal fertilized (Con) embryos. Our results revealed that Vc stimulated the expression of TET proteins in PA embryos. However, treatment with DMOG significantly inhibited the expression of TET proteins. In addition, 5hmC was increased following treatment with Vc and suppressed by DMOG in PA embryos. Taken together, these results indicate that the expression of TET proteins plays crucial roles mediated by 5hmC in PA embryonic development.